Predicting Lamina Yield from Logs of Different Diameters for Cross Laminated Timber Production - Jeong, Gi Young; Lee, Jun-Jae; Yeo, Hwanmyeong; Lee, So Sun (Journal of the Korean Wood Science and Technology, 2016)
The goal of this study was to predict lamina yield from logs of different diameter for production of cross laminated timber. Log characteristics of red pine (Pinus densiflora) and Japanese cedar (Cryptomeria japonica), including diameter, length, volume, and defects were used for statistical and geometrical analyses, along with the lamina characteristics, including width, thickness, and defects. Based on the data obtained, the strong factors influencing the yield and grade of lamina from the two species were statistically evaluated. A geometrical approach was used for analysis of the yield from logs of given diameters. Statistical analysis showed that lamina yield was dependent on target lamina size but the grade of lamina was not related to any of the log characteristics. The suggested yield equations from the geometrical approach indicated an accuracy of less than 20% difference. KCI Citation Count: 2